The environmental properties of radio-emitting AGN. Issue 3 (17th May 2018) - Magliocchetti, M; Popesso, P; Brusa, M; Salvato, M
ABSTRACT: We study the environmental properties of z ≲ 1.2 radio-selected active galactic nuclei (AGNs) belonging to the ∼2 deg 2 of the COSMOS field, finding that about 20 per cent of them appear within overdense structures. AGNs with $P_{1.4 \ \rm GHz}\gt 10^{23.5} \ \rm W\ Hz^{-1}\ sr^{-1}$ are twice more likely to be found in clusters with respect to fainter sources (∼38 per cent vs ∼15 per cent), just as radio-selected AGNs with stellar masses M *  > 10 11  M⊙ are twice more likely to be found in overdense environments with respect to objects of lower mass (∼24 per cent vs ∼11 per cent). Comparisons with galaxy samples further suggest that radio-selected AGN of large stellar mass tend to avoid underdense environments more than normal galaxies with the same stellar content. Stellar masses also seem to determine the location of radio-active AGN within clusters: ∼100 per cent of the sources found as satellite galaxies have M *  < 10 11.3  M⊙, while ∼100 per cent of the AGNs coinciding with a cluster central galaxy have M *  > 10 11  M⊙ . No different location within the cluster is instead observed for AGN of various radio luminosities. Radio AGN, which also emit in the Mid-Infrared show a marked preference to be found as isolated galaxies (∼70 per cent) at variance with those also active in the X-ray that all seem to reside within overdensities. What emerges from our work is a scenario whereby physical processes on sub-pc and kpc scales (e.g. emission, respectively, related to the AGN and to star formation) are strongly interconnected with the large-scale environment of the AGN itself.